Pluronics F-127/L-81 Binary Hydrogels as Drug-Delivery Systems: Influence of Physicochemical Aspects on Release Kinetics and Cytotoxicity - Oshiro, Alisson; Silva, Deyse C. da; Mello, Joyce C. de; Moraes, Vivian W. R. de; Cavalcanti, Leide P.; Franco, Margareth K. K. D.; Alkschbirs, Melissa I.; Fraceto, Leonardo F. [UNESP]; Yokaichiya, Fabiano; Rodrigues, Tiago; Araujo, Daniele R. de (Amer Chemical Soc, 2014)
We investigated the structure of the binary mixture of Pluronic F-127 (PL F-127) and Pluronic L-81 (PL L-81), as hydrogels for sumatriptan delivery and investigated the mixture possible use via subcutaneous route for future applications as a long-acting antimigraine formulation. We studied the drug micelle interaction by dynamic light scattering and differential scanning calorimetry, sol gel process by rheology, and small-angle X-ray scattering (SAXS). We also employed pharmaceutical formulation aspects by dissolution rate, release profile, and cytotoxicity studies for apoptosis and/or necrosis in fibroblasts (3T3) and neural cells (Neuro 2a). Mice liar hydrodynamic diameter studies revealed the formation of binary PL-micelles by association of PL F-127/PL L-81. The mixed micelle and binary hydrogels formation was also verified by only one phase transition temperature for all formulations, even in the presence of sumatriptan. The characterization of the hydrogel supramolecular organization by SAXS, rheology studies, and in vitro dissolution/release results showed a probable relationship between the transition of the lamellar to the hexagonal phase and the lower release constant values observed, indicating that PL L-81 participates in micelle-hydrogel formation and aggregation processes. Furthermore, the reduced cytotoxicity (annexin V-fluorescein isothiocyanate positive staining), with minor PL L-81 concentration, points to its potential use for the development of binary PL-systems containing sumatriptan capable of modulating the gelation process. This use may employ the minimum PL concentration and be interesting for pharmaceutical applications, particularly for migraine treatment.